Managing the Curriculum in Small Schools and Multi-Grade Classrooms - Mampane Tebogo Jillian; Carrim Ayesha (Journal of Education, Society & Multiculturalism)
The research examines the teaching challenges faced by rural, small multi-grade schools, which include logistical obstacles, insufficient resources, and a variety of learner requirements. Curriculum management in small multi-grade classrooms is the subject of this literature review research methodology paper. In these situations, educators are confronted with the necessity of developing novel educational approaches to address diverse learner requirements and resource constraints. The literature reviewed emphasizes the importance of curriculum management in ensuring the efficacy of teaching and the success of learners. The research endeavours to identify community support and participation in ensuring professional development methods in multi-grade schools. The literature results indicated that effective curriculum management enhances small and multi-grade education, as well as presents unique challenges and opportunities for educators. To optimise curriculum delivery in multi-grade classes, it is necessary to implement effective strategies and methodologies. Rural multi-grade classrooms can succeed with appropriate teaching practices and teacher professional development. The study concentrated on prior research on small multi-grade institutions. Curriculum management necessitates community support, differentiated instruction, and flexible planning. Schools may benefit from engagement with their communities and the adaptation of multi-grade teaching practices to meet local needs through the research initiative. The Ecological Systems Theory was employed as a prism to emphasise the numerous influences on multi-grade teaching and suggests that policymakers and educational leaders allocate professional development, curriculum adaptation, and collaborative planning time for small schools. Educator collaboration, resource funding, and specialised training programs for multi-grade teachers are all recommended. The research indicates that institutional reforms are necessary to guarantee that all learners have access to quality education, irrespective of their location, and to enhance the sustainability and success of rural and multi-grade education.